LAJU DEKOMPOSISI SERASAH DAUN DI KAWASAN HUTAN LARANGAN ADAT RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR SEBAGAI PENGEMBANGAN MODUL PEMBELAJARAN PADA KONSEP EKOSISTEM HUTAN TROPIS DI SMA KELAS X - Muhammad Abdillah Hanif Abdillah Hanif; Nursal '; Wan Syafi'i Syafi'i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted to determine the rate of leaf litter decomposition in Forest Areas native Prohibition Rumbio in September 2014 and January 2015. The study was conducted in two phases, phase field research and development of learning modules. Determination of the research station in purposive sample by three research stations as representing the forest community as a whole. At each station gets 15 bags of waste and the waste that is deposited on the forest floor litter bags were collected every interval of 15 days and dried for 75 days in the oven for 48 hours at a temperature of 700C – 750C. Each station measured soil temperature, soil moisture and pH of the soil and the types of trees on a plot measuring 20x20 m. The results showed the rate of leaf litter decomposition in Forest Areas native Prohibition Rumbio for 75 different days in each station, station 1 at a rate of waste decomposition leaf 0.0028 gr/m2/day, station 2 with a blade speed of waste degradation of 0.002 gr/m2/day, and the station 3 with the leaf litter degradation rate of 0.0018 gr/m2/day . The results of this study was developed as the development of learning modules on the concept of tropical forest ecosystems in the High School Class X. Key words: litter decomposition, forest Prohibition on Traditional Forest Rumbio, Learning Modules